Study of Equilibrium Time in Wetting Soil-Water Characteristics Curves (SWCC) using Capillarity Column Method - Nurjanah, Ina Asha; Kusumah, Rama Indera; Mina, Enden; Fathonah, Woelandari; Abdurohim, Abdurohim (Jurnal Fondasi, 2025)
The soil-water characteristic curve (SWCC) of soil plays the key roll in unsaturated soil mechanics which is a relatively new field. To encourage the geotechnical engineers to apply unsaturated soil mechanics theories in routine practice, numerical methods, based on the SWCC and saturated soil properties, have been developed to predict unsaturated permeability function and unsaturated shear strength properties which are expensive, time consuming, and it may require specials techniques or apparatus to measure the SWCC in laboratories. However, it is important to have laboratory measured data of SWCCs to enhance and verify the proposed numerical methods. Hence, employing the capillary column method which applies the tempe cell pressure principle, namely varying the matric suction value, this study aims to obtain the water content in each matric sauction variation which is then presented in SWCC form. Saturated permeability is obtained from constant head test. Permeability function is calculated indirectlt by Fredlund and Rahardjo method (1993) using SWCC and saturated permeability.